Psychometric Properties and Use of the Indonesian Florida Obsessive-Compulsive Inventory - Ticoalu, Christiana L.; Mar'at, Samsunuwijati; Suyasa, P. Tommy Y. S.; Storch, Eric A.; Goodman, Wayne K.; Hartanto, Steffi; Novrianto, Riangga; Jaya, Edo S. (UI Scholars Hub, 2024)
Presently, in Indonesia, the lack of a validated measure for obsessive–compulsive disorder (OCD) hinders diagnosis and treatment of the disease. The current study evaluated the reliability, validity, and optimal cut-off score of the Indonesian Florida Obsessive-Compulsive Inventory (FOCI) in predicting OCD presence. The participants included 384 adults: 157 with OCD, 80 case controls with anxiety or mood disorders, and 147 healthy controls. Assessments were conducted using FOCI, Obsessive-Compulsive Inventory-Revised, Patient Health Questionnaire-9, and Generalized Anxiety Disorder-7. Test–retest reliability of the FOCI was evaluated for over 2 weeks in 30 OCD patients. The internal consistency within OCD samples for the FOCI Symptom Checklist and Severity Scale was strong (Kuder–Richardson 20, KR-20 = 0.86; Cronbach’s alpha, α = 0.86), as well as the test–retest reliability (intraclass correlation coefficient [ICC] = 0.98 [95% CI: 0.95, 0.99] and ICC = 0.73 [95% CI: 0.49, 0.86], respectively). Convergent and discriminant validity were moderate to strong. Confirmatory Factor Analysis revealed a unidimensional factorial structure for the FOCI Severity Scale. A cut-off score of ≥5 predicted OCD with a sensitivity of 85% and specificity of 65%. Results support the use of Indonesian FOCI in screening and assessing OCD in Indonesian samples.